Hydrogeology of the Queenstown 1:500 000 map region (Sheet 3126) - Smart, Michael Charles (Rhodes University, Faculty of Science, Department of Geology, 1999)
The Groundwater characteristics of a portion of the Eastern Cape are depicted on a General Hydrogeological Map (Queenstown 3126) at 1 :500 000 scale. The purpose of the map and accompanying text is to provide a synoptic overview of the hydrogeology of the area. The "fractured and intergranular" aquifer type predominates in the more humid eastern part of the study area where the lithologies are more highly weathered whereas the fractured type predominates in the drier west. For the bulk of the area borehole yields are in the 0.5 - 2.0 ℓ/sec range. Higher yields (in the 2.0 - 5.0 ℓ/sec range) are common only in a small area in the south-west of the map. Lowest yields (0.1 - 0.5 ℓ/sec) are obtained in an area immediately north of East London and in the Dwyka Group near the NE coast. It is important to note that these yield ranges are merely a measure of the central tendency, and that higher yields - in excess of 3 ℓ/sec - could well be obtainable at optimal hydrogeological target features within these areas. Highest borehole yields are obtained in folded areas (restricted to the southern edge of the study area) followed by rocks with dolerite intrusions (common over the bulk of the study area). Other targets include fractured sedimentary and volcanic rock and unconsolidated deposits. Yields obtained from dolerite contact zones vary across the area; differences correspond to spatial variations in the style of intrusion. Highest success rates are obtained in areas intruded by a combination of dykes, ring-shaped sheets and irregular sheets while poor results are obtained in areas intruded by thick massive sills. Air photo and satellite image interpretation, geological mapping, magnetic, electrical resistivity and electromagnetic geophysical methods can be used to locate drilling target features. Groundwater quality is good since electrical conductivities over much of the area are lower than 70 mS/m and rarely exceed the South African Water quality guideline limit for human consumption of 300 mS/m. The volume of groundwater abstractable ranges between approximately 2 000 m³/km²/annum and 80 000 m³/km²/annum and is limited by either volumes of recharge or subsurface storage.
Keywords: Hydrogeology; Hydrogeology Maps; Hydrogeology -- South Africa -- Queenstown